E-COMMERCE DALAM PERSPEKTIF HUKUM ISLAM: ANALISIS FIKIH MUAMALAH TERHADAP PRAKTIK PERDAGANGAN DIGITAL - Arditya Prayogi; Qurrota A’yun; Alda Mafrikha Fauziah; Mohammad Fikri Fadilah; Maulidina Akmal; Amrina Rosyada; Riki Nasrullah (Wasīlah: Journal Of Sharia Sciences, 2026)
The development of digital technology has given rise to e-commerce as a new form of muamalah activity that is increasingly being used by society, including Muslims. The shift in transaction patterns from conventional to digital has given rise to various legal issues that require serious study from an Islamic legal perspective. This article aims to analyze the phenomenon of e-commerce from an Islamic perspective by examining the legal basis, reasons for permissibility, and the limitations of sharia that regulate it. This research uses a descriptive qualitative method with a literature study approach, through an analysis of classical and contemporary fiqh literature, books of schools of thought, fatwas of scholars, and academic sources relevant to digital buying and selling practices. The results of the study indicate that e-commerce is essentially permissible in Islam as long as it meets the pillars and requirements for a valid sale and purchase, such as clarity of the object, price, contract, and the willingness of the seller and buyer. Differences in views between schools of thought regarding the technicalities of the contract and the form of the transaction do not change the basic principles of the validity of muamalah as long as it does not contain elements of gharar, usury, and fraud. The implications of this study emphasize the importance of digital muamalah fiqh literacy for Muslims to be able to carry out e-commerce transactions legally, ethically, and responsibly in accordance with sharia values ​​in the digital era.